Perpindahan Minat Mahasiswa Terhadap Penggunaan Aplikasi E-Wallet Sebelum dan Setelah Perkuliahan Luring di Masa Pandemi Covid - Sihombing, Abednego; Mardianto, M. Fariz Fadillah; Inneztiana, Alya Rahma; Girsang, Anne Vinella; Br Pangaribuan, Fani Agustina; Panjaitan5, Leni Sartika; Adriansyah, Muhammad Haykal (Zeta - Math Journal, 2023)
Technological advances in the field of financial innovation, namely e-wallets, provide convenience and practicality in making transactions online. The use of e-wallets is popular among students, one of which is the Faculty of Science and Technology, Airlangga University. Students with interests or tastes in the type of e-wallet and the running of all activities offline make it very likely that there will be a change in student interest from one e-wallet to another e-wallet. The change in interest will be analyzed with the Markov chain transition probability. The data in this study is primary data by conducting an online survey of 100 respondents in the form of a g-form given to students of the Faculty of Science and Technology, Airlangga University. Based on the results of the Markov chain transition opportunities, it can be concluded that the use of e-wallet applications can move according to the advantages of e-wallet applications in each region. This change in interest in e-wallet application users occurs because the application of choice is an application that provides easy access, lots of discounts, small admin fees, and others.